Incipient diploidization of the medicinal plant Perilla within 10,000 years - Yujun Zhang (Nature Portfolio, 2021)
Perilla is a young allotetraploid species within the mint family Lamiaceae. Here, the authors assemble the genomes of a tetraploid species and its diploid progenitor, characterize the incipient diploidization of the tetraploid, conduct population genetics analyses, and identify loci associate with pigmentation and oil content.